Management and the Size of the Firm - Ross, N. S. (Review of Economic Studies, 1952)
Journal Article Management and the Size of the Firm Get access N. S. Ross N. S. Ross Cardiff Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 3, 1952, Pages 148–154, https://doi.org/10.2307/2296017 Published: 01 January 1952